Sporting Clube de Portugal, a social media benchmark in the football clubs’ sector - Saúde, Miguel Lages Ribeiro de Gomes (2016)
In today’s world, it is becoming more prominent the importance that Internet and social media have been having in society and in the lives of each individuals who compose it. With the exponential increase in the number of users and with the emergence of new social networks, football clubs have seen in these platforms the possibility to communicate in a not very expensive way to an audience of thousands or millions of fans in a fairly segmented form. Portugal is no exception and in a better or worse manner, the majority of the Portuguese League clubs are already present in the most popular social networks. This case study, based on the theme referred above, seeks to portray how Sporting Clube de Portugal has changed its marketing strategy in the last years by shaping it around the club’s fans, revealing a strong focus on the online component and more specifically on social networks. On that basis, it will be presented the progress of the club in the various platforms, from the moment of its creation to the present day, intending to show that in general, Sporting CP’s presence in social media can be considered not only as a national but also as an international benchmark. To contribute for a generic comprehension of the case study, a literature review will highlight the main concepts of sports marketing, the importance of fans and how they relate to football clubs and finally the growth of social media in the Internet.